Biliary Cripple and the Spectrum of Complications following Cholecystectomy: A Case Report - Anish Kumar Shrestha; Jayant Kumar Sah; Bikal Ghimire; Aashna Bhandari; Anisha Shrestha (Case Reports in Surgery)
Bile duct injury is a complication seen during cholecystectomy. Here, we highlight the occurrence of bile duct injury (BDI) during an open cholecystectomy who underwent hepaticojejunostomy (HJ), later presenting with a stricture of HJ. Percutaneous transhepatic biliary drainage (PTBD) was performed which led to the development of hepatic artery injury.